GREEKS, ROMANS AND BARBARIANS - Cunliffe, Barry W. Link ([S.l.])
1 online resource
Keywords: Greeks, Romans and Barbarians (1988) explores a number of themes that bind the regional cultural developments of mainland Europe and the Mediterranean Basin. Rejecting the separation into two distinct disciplines for the study of the Mediterranean world and the barbarian communities of northern Europe, this book looks at the systems at work in society - economic strategies, the nature of exchange and trade, the relationships between a civilised core and its periphery - and, more importantly, by the changing trajectories of the socio-economic systems. It also examines how much the physical nature of Western Europe affected these systems, as contacts and trade moved through some regions but were obstructed in others.